Effects of clonal integration and nutrient availability on the growth of Glechoma longituba under heterogenous light conditions - Zhang, Rui; Chen, Zhi-Huan; Li, Yu-Meng; Wang, Ning; Cui, Wen-Tao; Zhao, Bing-Nan; Si, Chao (Frontiers in Plant Science, 2023)
Clonal integration of connected ramets within clones is an important ecological advantage. In this study, we tested the hypothesis that the effects of clonal integration on performance of donor and recipient ramets when one resource is heterogeneous can be influenced by the availability of another resource of donor ramets. We conducted a greenhouse experiment on the widespread, perennial herb Glechoma longituba. Clonal fragments consisting of pairs of connected ramets were grown for seven weeks. The younger, apical ramets were exposed under 30% or 100% light condition and the older, basal ramets were treated with three levels of nutrients. The connections between ramets were either severed or left intact. 30% light condition negatively affected the growth of apical ramets, basal ramets and the whole fragments. Clonal integration significantly increased the growth of apical ramets, but decreased the growth of the basal ramets. Medium and high level nutrient availability of basal ramets significantly increased the growth of apical ramets, basal ramets and the whole fragments. At the high nutrient level, the reduction in growth of basal ramets from clonal integration was decreased, but the growth responses of apical ramets and the whole fragments to clonal integration were not influenced by nutrient availability. The results suggested that clonal integration was benefit to the growth of apical ramets of Glechoma longituba but at the cost of reducing the growth of basal ramets. Although the high nutrient level could reduce the cost that clonal integration brought to the unshaded basal ramets, but could not increase the benefit that clonal integration brought to the shaded apical ramets and whole fragment.